2018
DOI: 10.17816/ped9222-29
|View full text |Cite
|
Sign up to set email alerts
|

Complementary food - important components of the child’s ration: effects on health and ways of optimization

Abstract: Relevance of the research. Timing, order and sequence of complementary feeding remain the subject of discussion until now. The aim of the study. Estimate influence of different outlines of introduction of complementary foods on nutritional status and food behavior in children of first year of life. Materials and methods. Examined 96 children in age of 4-6 months during introduction of complementary foods. Main group – 50 children (27 breast-feed (BF) children and 23 on milk formulas (MF)), in whose diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
0
0
2
Order By: Relevance
“…Moreover, over 100% PVAC retention was also observed after boiling or steaming provitamin A biofortified pumpkin (Carvalho et al 2015). Studies by Carvalho et al (2014) and Carvalho et al (2015) are consistent with several other studies that showed that PVAC retention was over 100% in pumpkin puree prepared from either boiled or steamed pumpkin (Bulatova et al 2018;Buzigi, Pillay, and Siwela 2020a;Maier et al 2008;Provesi, Dias, and Amante 2011). The higher retention of b-carotene content observed in cooked pumpkin may be due to the cis-b-carotene isomers that increase on heating PVAC rich foods (Azizah et al 2009;Bechoff et al 2017;Bengtsson et al 2008;De Moura, Miloff, and Boy 2015;Mugode et al 2014).…”
Section: Home Cooking Methodssupporting
confidence: 65%
“…Moreover, over 100% PVAC retention was also observed after boiling or steaming provitamin A biofortified pumpkin (Carvalho et al 2015). Studies by Carvalho et al (2014) and Carvalho et al (2015) are consistent with several other studies that showed that PVAC retention was over 100% in pumpkin puree prepared from either boiled or steamed pumpkin (Bulatova et al 2018;Buzigi, Pillay, and Siwela 2020a;Maier et al 2008;Provesi, Dias, and Amante 2011). The higher retention of b-carotene content observed in cooked pumpkin may be due to the cis-b-carotene isomers that increase on heating PVAC rich foods (Azizah et al 2009;Bechoff et al 2017;Bengtsson et al 2008;De Moura, Miloff, and Boy 2015;Mugode et al 2014).…”
Section: Home Cooking Methodssupporting
confidence: 65%
“…Мясные детские консервы выпускаются на основе дозволенного мяса молодых и здоровых животных, вскормленных на естественной пище без кормовых добавок, в питание включены важные витамины и минералы. Существуют специальные консервы, натуральные источники легкоусвояемого железа, приготовленные на основе молодой говядины, для малышей с железодефицитной анемией или нуждающиеся в ее профилактике [1,4,8].…”
Section: «халяль» -не только мясоunclassified
“…При этом дети на грудном вскармливании легче воспринимают новые продукты и новые вкусы по сравнению с детьми, получавшими искусственное вскармливание. Постепенно прикорм «учит» ребенка есть самостоятельно и переходить к повседневным продуктам [11][12][13].…”
unclassified
“…Поэтому в период введения новых продуктов питания крайне важно предоставлять детям свободу выбора в процессе приема пищи, делать перерывы в кормлении, если ребенок устал, позволять ребенку играть или отвлекаться во время кормления. Возможны некоторые послабления в отношении «любимой» и «нелюбимой» пищи [13][14][15]. Все это позволит избежать возникновения в раннем возрасте негативного отношения к новой пище.…”
unclassified